2021
DOI: 10.1093/bjs/znab323
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health technology for remote home monitoring after surgery: a meta-analysis

Abstract: Background Mobile health (mHealth) technology has been proposed as a method of improving post-discharge surveillance. Little is known about how mHealth has been used to track patients after surgery and whether its use is associated with differences in postoperative recovery. Methods Three databases (PubMed, MEDLINE and the Cochrane Central Registry of Controlled Trials) were searched to identify studies published between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 70 publications
0
26
1
2
Order By: Relevance
“…A recent meta-analysis analyzed 45 studies in which mobile telemonitoring was performed in patients postsurgery. 4 Although there was no difference in the number of outpatient visits, there was a significant reduction in hospital (odds ratio: 0.47, 95% confidence interval: 0.29-0.79) and ED visits (odds ratio: 0.42, 95% confidence interval: 0.23-0.79) in the pooled analysis; however, there were no differences in complications. Of note, only a few individual studies have found differences in outcomes between groups, including patients who underwent transplant and total knee and hip arthroplasty.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent meta-analysis analyzed 45 studies in which mobile telemonitoring was performed in patients postsurgery. 4 Although there was no difference in the number of outpatient visits, there was a significant reduction in hospital (odds ratio: 0.47, 95% confidence interval: 0.29-0.79) and ED visits (odds ratio: 0.42, 95% confidence interval: 0.23-0.79) in the pooled analysis; however, there were no differences in complications. Of note, only a few individual studies have found differences in outcomes between groups, including patients who underwent transplant and total knee and hip arthroplasty.…”
Section: Discussionmentioning
confidence: 75%
“…They reported substantial financial savings, a 75% reduction in clinic appointments, and a 97% patient satisfaction score. Additionally, a recent meta-analysis conducted by Dawes et al 4 including 45 remote monitoring studies focused on mobile telemonitoring, reported broad adherence rates, improved quality of life, and decreased readmissions and emergency department (ED) visits. However, they note limitations, including that only 11 studies identified postoperative outcomes, heterogeneity of outcome measures, and weak study designs.…”
mentioning
confidence: 99%
“…The users of telemedicine technologies in posthospital patient care process after THA are patients (at every stage of the process), physicians [ 13 , 14 , 23 , 24 , 38 ], physiotherapists [ 15 , 16 , 24 , 25 , 26 ], surgeons, [ 17 , 18 , 25 ], surgeon’s administrative assistants [ 17 ], health care team [ 27 ], and rehabilitation center [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Remote home monitoring via mHealth is feasible, adaptable, and may even promote more effective postoperative care. Given the rapid expansion of mHealth, physicians and policymakers need to understand these technologies better so that they can be integrated into high-quality clinical care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kane et al found that failure to achieve baseline step counts was associated with risk of readmission in colorectal surgery patients ( 37 ). A meta-analysis of studies in mobile health applications used by postoperative patients demonstrated reduced emergency department visits and hospital admissions ( 38 ). Meanwhile, deep learning has been trained to recognize skin lesions at a degree comparable to board-certified dermatologists ( 39 ).…”
Section: Introductionmentioning
confidence: 99%